Self-Measured Blood Pressure and Target Organ Damage in Newly Detected Hypertension in South Gujarat, India - Harshil Patel; Ashok Gagiya; Vivek Gurjar; Chintan Patil (Medsci Publications, 2023)
Introduction: Blood pressure transient spikes have been considered to be noise and only a hindrance to a proper assessment of typical blood pressure, which is defined as the actual underlying average blood pressure over a long period of time. The current study aimed to see if the highest Self measured Systolic blood Pressure could be utilized to forecast the occurrence of Target organ damage and evaluate the independent association between the maximum Self measured Systolic blood Pressure and Target organ damage in individuals with untreated hyper-tension. Method: We evaluated the urine albumin/creatinine ratio (UACR) and carotid intima-media thickness (IMT) us-ing ultrasonography in 462 hypertensive individuals who had never taken treatment for their hypertension. Resi-dential blood pressure was recorded. Result: The maximal Self measured Systolic blood Pressure had considerably higher association coefficients with left ventricular mass index (LVMI) and carotid intima-media thickness than the mean Self measured Systolic blood Pressure. Irrespective of the mean Self measured Blood pressure level, multivariate regression studies showed that the maximal Self measured Systolic blood Pressure was independently related with left ventricular mass index and carotid intima-media thickness. Conclusion: Transiently high blood pressure measurements recorded at Self measured shouldn't be dismissed as noise but rather taken seriously as significant warning signs of hypertensive Target organ damage in the heart and arteries.